(untitled) (Texas Journal of Engineering and Technology, 2022)
The article covers the tool change systems of the group of lathe machines, where equipment manufactured by Colombo, Baruffaldi, Duplomatic and Sauter have wide application in design of machines, as well as algorithm for changing the tool for revolver heads of lathe machines is given